A efetividade do direito fundamental à saúde pelo Instituto do Amicus Curiae - Santos, Ana Victoria da Cunha (2021)
The supremacy of the Constitution in the normative Brazilian legal system, although it must ensure integration, presents gaps, incompleteness and imperfections. That is to say, the science of law, whose pedestal is CF/88, is not the only possible reality, as it also depends on other institutions and fields of knowledge, so that different realities are shown and revealed. In this way of thinking, it is argued that, for a real fulfillment and satisfaction of the fundamental right to health, in which the principle of the dignity of the human person is based, efficient communication between the State and the citizen is necessary, in a relationship dialectic, which presupposes democratic participation. If the legal order is formed by a dynamic system, that is, by a vast solidary set of elements produced to be determined and adaptable to changes in the environment where it operates, the right to health must also be carefully observed by the members of the State's social environment. The need to search for mechanisms to increase social participation in constitutional jurisdiction in the case of amicus curiae is emphasized, since it is assumed that certain agents do not participate in the public debate. For this analysis, the open society theory of interpreters of the constitution of Peter Häberle is used as a reference, according to which, the interpretation must be given in a plural way, so that it reaches the largest possible number of interpreters. In conclusion, it is necessary to welcome social participation in constitutional jurisdiction implodes the feeling of democracy. For this reason, an open society of interpreters of the constitution is understood as an ideal hermeneutic to be built daily and daily, a fact that cannot be ignored its limitations.